'Last of the Schoolmen': The Young Marx, Latin Culture, and the Doctoral Dissertation. Issue 1 (2nd January 2023) - Barbour, Charles
ABSTRACT: This article examines Marx's earliest writings, especially his doctoral dissertation on "The Difference Between the Democritean and Epicurean Philosophy of Nature" and the notebooks he kept while preparing it. Previous commentators on this material have tended to take one of two approaches: either they have used it to associate Marx with an expansive and abstract Western Tradition of philosophical inquiry, or they have located it in the narrow context of the intellectual culture of the German Vormärz . Here I seek to mediate between these extremes. These documents, I argue, suggest that Marx was less a part of a Western Tradition, or a set of abstract normative debates that ostensibly stretches from the ancients to modernity, than of what I call Latin Culture, or a Latin-speaking culture that was inscribed in practices, norms, and institutions, and that persisted in Europe from late antiquity into the nineteenth century. Placing Marx's early writings in this context helps explain some of the tensions that characterise his thought and to clarify the practical consequences of what might otherwise appear as purely theological and metaphysical speculations.